Fragments de passioner i de leccionari del santoral de la Biblioteca Episcopal de Vic dels segles IX-XIII - Gros i Pujol, Miquel dels Sants (Miscel·lània litúrgica catalana, 2018)
No complete 9th-13th century passionary or lectionary of the sanctorale of the present-day Catalan churches has been preserved. This makes the 40 manuscript fragments of this type of liturgical texts from these centuries, now kept in the Vic Episcopal Library, highly valuable for the study of such books. In this paper, in addition to identifying their content and specifying their date, the description of these fragments gives the codicological characteristics of each piece to provide researchers with the clearest possible idea of the manuscript from which they come.